Antibodies Against β2-Glycoprotein I Complexed With an Oxidised Lipoprotein Relate to Intima Thickening of Carotid Arteries in Primary Antiphospholipid Syndrome. Issue 1 (2006) - Ames, P. R. J.; Alves, J. Delgado; Lopez, L. R.; Gentile, F.; Margarita, A.; Pizzella, L.; Batuca, J.; Scenna, G.; Brancaccio, V.; Matsuura, E.
Abstract : To explore whether antibodies against β2 -glycoprotein I (β2 GPI) complexed to 7-ketocholesteryl-9-carboxynonanoate (oxLig-1) and to oxidised low-density lipoproteins (oxLDL) relate to paraoxonase activity (PONa) and/or intima media thickness (IMT) of carotid arteries in primary antiphospholipid syndrome (PAPS). As many as 29 thrombotic patients with PAPS, 10 subjects with idiopathic antiphospholipid antibodies (aPL) without thrombosis, 17 thrombotic patients with inherited thrombophilia and 23 healthy controls were investigated. The following were measured in all participants: β2 GPI−oxLDL complexes, IgG anti-β2 GPI−oxLig-1, IgG anti-β2 GPI−oxLDL antibodies (ELISA), PONa, (para-nitrophenol method), IMT of common carotid (CC) artery, carotid bifurcation (B), internal carotid (IC) by high resolution sonography. β2 GPI−oxLDL complex was highest in the control group ( p < 0.01), whereas, IgG anti-β2 GPI−oxLig1 and IgG anti-β2 GPI−oxLDL were highest in PAPS ( p < 0.0001). In healthy controls, β2 GPI−oxLDL complexes positively correlated to IMT of the IC ( p = 0.007) and negatively to PONa after correction for age ( p < 0.03). PONa inversely correlated with age ( p = 0.008). In PAPS, IgG anti-2GPI−oxLig-1 independently predicted PONa ( p = 0.02) and IMT of B ( p = 0.003), CC, ( p = 0.03) and of IC ( p = 0.04). In PAPS, PONa inversely correlated to the IMT of B, CC and IC ( p = 0.01, 0.02 and 0.003, respectively). IgG anti-2GPI−oxLig-1 may be involved in PAPS related atherogenesis via decreased PON activity.